The Mascot of the Nusantara Keris Museum as a Socio-Cultural Symbol - Wirantoni, Wirantoni; Panindias, Asmoro Nurhadi (LPPM Universitas PGRI Sumatera Barat, 2024)
Mascots play an important role as a promotional tool as well as a visual representation that reflects the museum's identity as a whole, including the cultural values, history, and communities involved. This study aims to design a socio-cultural symbol that can be realized in the form of a mascot for the Nusantara Keris Museum through the design thinking design method from David Kelley. This mascot is designed to represent the socio-cultural elements of Surakarta City, including the friendly character of the community and other local wisdom, such as physical relics in the form of artifacts, historical buildings, and cultural areas. In addition, mascots can also reflect intangible heritage, such as traditional music, dance, and various religious rituals and traditions (Purnomo et al., 2023). These elements can be evaluated in depth to ensure that the resulting mascot can function as an appropriate symbol and represent the socio-cultural wealth of Surakarta.